LEGAL DUALISM MARRIAGE REGISTRATION FOR MUSLIMS IN INDONESIA - M. Zamroni (Jurnal Reformasi Hukum : Cogito Ergo Sum, 2018)
Marriage has a great significance in human life and the cultural patterns to control and establish a strong foundation in the household. There is a duality of the legal status of marriage to nationals of Indonesia, especially Islam, which is a valid marriage and recorded in the sub-district religious affairs office with a valid marriage according to the norms of Islam but is not listed on the state agencies. Legitimacy of marriage has legal implications of the status of children who are born, as well as inheritance rights affected, and the recording of the key events in the system of administration. This study uses the methodology of normative juridical deduction, the judicial approach. At the end of the discussion will be found the answer from the legal issues that the law of the State Administraon that marriage registration is administrative actions based on the legislation in force undertaken by the competent instasi. With prescriptions for a legal solution.